2013
DOI: 10.1080/15659801.2013.892297
|View full text |Cite
|
Sign up to set email alerts
|

Early physical maturation of female common bottlenose dolphin Tursiops truncatus in the eastern Levantine Basin

Abstract: Regional resource limitation in the eastern Levantine Basin was predicted to protract the growth of members of the Israeli sub-population of the common bottlenose dolphin (CBD), compared to CBD sub-populations of similar adult size. Growth curves were fitted to length-at-age data available for 24 male and 26 female CBD stranded or incidentally caught along the Israeli coastline between 2000 and 2009. The obtained model growth constants were compared to those of other CBD subpopulations from the southeastern co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…7), and it is also distinct in rapid early growth and maturation. Thus, growth rates for both sexes, as indicated by k values in the Gompertz equation, are extremely high in comparison with other populations (Kerem et al 2013). Given a small adult body size, such a growth curve is a manifestation of an extremely re production-oriented life history of a marine mammal.…”
Section: Life-history Strategiesmentioning
confidence: 93%
See 3 more Smart Citations
“…7), and it is also distinct in rapid early growth and maturation. Thus, growth rates for both sexes, as indicated by k values in the Gompertz equation, are extremely high in comparison with other populations (Kerem et al 2013). Given a small adult body size, such a growth curve is a manifestation of an extremely re production-oriented life history of a marine mammal.…”
Section: Life-history Strategiesmentioning
confidence: 93%
“…7): rapid early growth and fast attainment of the relatively small asymptotic size. However, the environmental conditions in the eastern Mediterranean, which were suggested as possible causes of such an early maturation of females (Kerem et al 2013), are substantially different from the Black Sea: the Levantine basin is warmer, less productive and more saline. Meanwhile, the male growth curve is closer to that of the dolphins from the Mississippi region of the Gulf of Mexico (data by Mattson et al 2006) (Fig.…”
Section: Life-history Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Not all bottlenose dolphins reach maximum size at the same age (Read et al 1993), and thus it is possible some of the mothers born into the population between 1990 and 2012 would have continued to grow past 8 yr of age. Females often reach asymptotic length before males (Read et al 1993), and Kerem et al (2013) have shown that 99% of growth in female bottlenose dolphin occurs before 6 yr. Additionally, growth rates slow dramatically as dolphins approach asymptotic length (Read et al 1993, Chong & Schneider 2001. Hence, any increases in mother size over the study are likely to be negligible.…”
Section: Modellingmentioning
confidence: 99%